Practical Absorbing Boundary Conditions for Wave Propagation on Arbitrary Domain (Advances in Applied Mathematics and Mechanics, 2021)
This paper presents an absorbing boundary conditions (ABCs) for wave propagations on arbitrary computational domains. The purpose of ABCs is to eliminate the unwanted spurious reflection at the artificial boundaries and minimize the finite size effect. Traditional methods are usually complicate in theoretical derivation and implementation and work only for very limited types of boundary geometry. In contrast to other existing methods, our emphasis is placed on the ease of implementation. In particular, we propose a method for which the implementation can be done by fitting or learning from the simulation data in a larger domain, and it is insensitive to the geometry and space dimension of the computational domain. Furthermore, a stability criterion is imposed to ensure the stability of the proposed ABC. Numerical results are presented to demonstrate the effectiveness of our method.